2016
DOI: 10.1126/scitranslmed.aad7785
|View full text |Cite
|
Sign up to set email alerts
|

Deglycosylated bleomycin has the antitumor activity of bleomycin without pulmonary toxicity

Abstract: Bleomycin (BLM) is a potent anticancer drug used to treat different malignancies, mainly lymphomas, germ cell tumors, and melanomas. Unfortunately, BLM has major, dose-dependent, pulmonary toxicity that affects 20% of treated individuals. The most severe form of BLM-induced pulmonary toxicity is lung fibrosis. Deglyco-BLM is a molecule derived from BLM in which the sugar residue d-mannosyl-l-glucose disaccharide has been deleted. The objective of this study was to assess the anticancer activity and lung toxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 31 publications
(36 reference statements)
2
19
0
Order By: Relevance
“…The pro-inflammatory cytokines are known to play a significant role in the processing of pulmonary fibrosis, including TNF-α and IL-6. Furthermore, the excessive free radicals will result in oxidative stress or chronic inflammation [1,2,35], the related enzymes have a significant function in the processing of lung fibrosis, and thus, the activities of the oxidant enzymes (MPO and MDA) were also measured in this study. The results showed that CI SCFE combined with BLM could distinctly decrease the levels of inflammatory cytokines (TNF-α, IL-6) and oxidant enzymes (MPO, MDA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pro-inflammatory cytokines are known to play a significant role in the processing of pulmonary fibrosis, including TNF-α and IL-6. Furthermore, the excessive free radicals will result in oxidative stress or chronic inflammation [1,2,35], the related enzymes have a significant function in the processing of lung fibrosis, and thus, the activities of the oxidant enzymes (MPO and MDA) were also measured in this study. The results showed that CI SCFE combined with BLM could distinctly decrease the levels of inflammatory cytokines (TNF-α, IL-6) and oxidant enzymes (MPO, MDA).…”
Section: Discussionmentioning
confidence: 99%
“…However, BLM exhibits the main side effect of dose-dependent pulmonary toxicity, which affects 20% of treated individuals. Pulmonary fibrosis is a severe form of lung toxicity, which was induced by BLM [2]. However, the etiology and mechanism of pulmonary fibrosis have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of caspase-1/IL-1β in BLM-induced lung toxicity has already been reported in animal models [16, 17]. Recently, structural cells have been reported to be involved in capsase-1 activation and IL-1β secretion in the lung following different profibrotic stimuli [18, 19]. Mesothelial cells have already been shown to be involved in the initiation of the inflammatory response in a model of talc-induced pleurodesis [28].…”
Section: Discussionmentioning
confidence: 99%
“…For Il-1β assessment in supernatant, cells were treated with BLM in serum-free medium. When indicated, caspase-1 was blocked using YVAD (Bachem AG) as previously described [19]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation